Sensitive detection of organic pollutants by advanced nanostructures - Cialla-May, Dana; Weber, Karina; Popp, Jürgen (Elsevier, 2019)
The sensitive detection of organic pollutants is introduced by employing advanced nanostructures in electrochemical, colorimetric, and optical sensing schemes. As target analytes, hydrocarbons (e.g., polycyclic aromatic hydrocarbons (PAHs)), organic solvents, volatile organic compounds (VOCs), persistent organic pollutants such as pesticides as well as relevant compounds from industrial production and wastewater treatment are discussed. For the molecule classes the most applied sensing strategy is identified, for example, surface-enhanced Raman spectroscopy for the detection of PAHs or resistance-based techniques for the analysis of VOCs. In tabular overviews, the limits of detection as well as sensing platform and measurement conditions are summarized for the largely addressed targets, that is, PAHs, VOCs, and pesticides.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Hydrocarbons; Nanostructures for sensing applications; Organic solvents; Persistent organic pollutants; Pollution due to industrial production; and water treatment; Polycyclic aromatic hydrocarbons; Volatile organic compounds (VOCs)